Current State of the Rare Earth Industry in Russia and Siberia; Procedia Chemistry; Vol. 11 : 1st International Symposium on Inorganic Fluorides: Chemistry and Technology, ISIF 2014, Tomsk, Russia - Buinovsky (Buynovskiy, Buinovskii) A. S. Alexander Sergeevich; Zhiganov A. N.; Sofronov V. L. Vladimir Leonidovich; Sachkov V. I.; Daneykina (Daneikina) N. V. Natalia Viktorovna (2014, 2014)
Title screen